2018
DOI: 10.1080/10408398.2018.1427044
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ginger intake on weight loss and metabolic profiles among overweight and obese subjects: A systematic review and meta-analysis of randomized controlled trials

Abstract: This systematic review and meta-analysis of randomized controlled trials (RCTs) was performed to summarize the effect of ginger intake on weight loss, glycemic control and lipid profiles among overweight and obese subjects. We searched the following databases through November 2017: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and assessed for quality of the studies according to the Cochrane risk of bias tool. Data were pooled using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 31 publications
3
51
0
3
Order By: Relevance
“…Ginger (Zingiber officinale) is a perennial herbaceous plant widely distributed in India, East Asia, and Southeast Asia and is used as a pungent flavoring spice. Ginger has been shown to have antioxidant (Danwilai et al, 2017), anti-inflammatory (Zehsaz et al, 2014), anti-cancer (Pashaei-Asl et al, 2017), neuroprotective (Saenghong et al, 2012), anti-emetic (Saberi et al, 2014), and antihyperglycemic effects (Maharlouei et al, 2018). In addition, anti-obesity effects of ginger have been reported in many preclinical and clinical studies (Maharlouei et al, 2018;Misawa et al, 2015;Nammi et al, 2009;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ginger (Zingiber officinale) is a perennial herbaceous plant widely distributed in India, East Asia, and Southeast Asia and is used as a pungent flavoring spice. Ginger has been shown to have antioxidant (Danwilai et al, 2017), anti-inflammatory (Zehsaz et al, 2014), anti-cancer (Pashaei-Asl et al, 2017), neuroprotective (Saenghong et al, 2012), anti-emetic (Saberi et al, 2014), and antihyperglycemic effects (Maharlouei et al, 2018). In addition, anti-obesity effects of ginger have been reported in many preclinical and clinical studies (Maharlouei et al, 2018;Misawa et al, 2015;Nammi et al, 2009;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intake of capsaicinoids decreased body weight through reductions in energy intake (Whiting et al, 2014). In another meta-analysis study, taking ginger by obese people decreased body weight, WC, HR, fasting glucose, and insulin resistance, and increased HDL-cholesterol, whereas did not influence insulin, BMI, triglycerides, total- and low-density lipoprotein (LDL)-cholesterol concentrations (Maharlouei et al, 2018). Moreover, catechins intake reduced weight as well as maintained weight after a period of weight loss (Hursel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta‐analysis by Maharlouei et al . reported that ginger significantly decreased BW (Standardized Mean Difference (SMD): −0.66; 95% CI: −1.31, −0.01; P = 0.04) and waist‐to‐hip ratio (SMD: −0.49; 95% CI: −0.82, −0.17; P = 0.003) . Ginger is generally considered a safe herbal medicine and recently it has been shown that [6]‐gingerol, one of the major components of fresh ginger, is endowed with strong anti‐oxidant action both in vivo and in vitro , in addition to strong anti‐inflammatory and anti‐apoptotic actions …”
Section: Discussionmentioning
confidence: 99%
“…12 A systematic review and meta-analysis by Maharlouei et al reported that ginger significantly decreased BW (Standardized Mean Difference (SMD): −0.66; 95% CI: −1.31, −0.01; P = 0.04) and waist-to-hip ratio (SMD: −0.49; 95% CI: −0.82, −0.17; P = 0.003). 31 Ginger is generally considered a safe herbal medicine 32 and recently it has been shown that [6]-gingerol, one of the major components of fresh ginger, is endowed with strong anti-oxidant action both in vivo and in vitro, in addition to strong anti-inflammatory and antiapoptotic actions. 33 G. cambogia, the third most common ingredient in the current study, contains HCA, which has been shown to inhibit citrate cleavage enzyme, suppress de novo fatty acid synthesis and food intake, and consequently decrease BW gain.…”
Section: Discussionmentioning
confidence: 99%